PELVIC PHYSIOTHERAPY PERFORMANCE IN THE TREATMENT OF VOIDING AND SEXUAL DYSFUNCTIONS IN PROSTATECTOMIZED PATIENTS: INTEGRATIVE REVIEW - de França, Rocilda Nogueira (2021)
In recent years there has been a prevalence of prostate cancer in the male population, mainly affecting men over 65 years of age. The main surgical treatment is total radical prostatectomy. As with any other surgery, risks and harmful consequences may occur, as the procedure can harm the urogenital system. Pelvic physiotherapy acts as a conservative treatment, aimed at rehabilitating the voiding and sexual function of these individuals. This is an integrative literature review, with the aim of conducting a survey of physical therapy interventions used in disorders caused by surgery, published in the last 10 years. The search took place in the following databases: BVS, Scielo, Pubmed and Pedro, through the descriptors and their combinations, Prostatectomy, Physiotherapy, Urinary Incontinence, and Erectile Dysfunction. A total of 337 articles were found with the crossing of descriptors, but only 184 were published in the last 10 years. The final sample, after applicability of the inclusion and exclusion criteria, resulted in 12 articles. Pelvic floor muscle training, electrical stimulation, biofeedback, pilates and behavioral therapy were observed as physical therapy interventions used in conservative treatment; it was noticed that the associated therapies were more effective against voiding dysfunction, however, in sexual dysfunction, pelvic physiotherapy does not have a full effect on erectile dysfunction; it can be concluded that physiotherapeutic interventions are of great importance in the treatment of voiding and sexual dysfunctions, as it enables patients to return to their urinary functions, despite not promoting a total improvement in their sexual function.